Crescimento, aspectos nutricionais e fotossintéticos de plantas jovens de bertholletia excelsa h. b. submetidas à diferentes tratamentos de fertilização - Corrêa, Viviane Maia (Instituto Nacional de Pesquisas da Amazônia - INPA, 2013)
The chestnut (Bertholletia excelsa H. B.) has been one of the native species most used for composing agroforestry and homogeneous plantations in the Amazon region due its excellent silvicultural characteristics, but there are few studies that address the responses of species, from the point of view of performance and physiological growth when subjected to fertility treatments. The objective of this research was to investigate the responses of growth, nutritional aspects and photosynthetic characteristics of young plants of Bertholletia excelsa under different fertilization treatments. The experiment was carried on a greenhouse, the plants were grown in Oxisol of loamy soil. The treatments were: T1 (control - without fertilizer), T2 (Ca and Mg), T3 (Ca, Mg, K, N + micronutrients), T4 (Ca, Mg, K, N, 100 mg kg-1 of P + micronutrients ), T5 (Ca, Mg, K, N, 200 mg kg-1 of P + micronutrients), T6 (Ca, Mg, K, N, 400 mg kg-1 of P + micronutrients), T7 (Ca, Mg, K, N, 500 mg kg-1 of P + micronutrients. Besides the analysis of soil fertility, were also studied growth in height and diameter, the gain index leaf, the main root length, leaf area, specific leaf area and accumulation of plant dry matter and leaf nutrient content, the efficient use of nutrients, gas exchange, the pigment contents, chlorophyll fluorescence levels of soluble sugars and starch. Regarding the growth in height and diameter, while the treatment T1 grew in height 3.0 cm month-1, T6 and T7 treatments stood out with monthly growth rates of the order of 7.9 to 7.6 cm month-1, while that the diameter for these treatments exhibited monthly increase of 0.4 (T1), 0.9 (T6) and 0.8 (T7) mm month-1. Treatments T5, T6 and T7 stood out for biomass and leaf area showed up to three times greater than T1. Length of the main and root/PA root ratio was higher in the T1 (0,48 and 94.1 cm), whereas in the T6 values for these two parameters were 0.16 and 38,0 cm2. Treatments showed significant differences in specific leaf area. Regarding nutrient content, T1, T6 and T7 had the highest levels of P. The maximum photosynthetic rates ranged between 7.3 and 11,0 mol m-2 s-1, with the highest rates observed in T1, T6 and T7. Chlorophyll contents were higher in the treatment T5 (2.87 g mol-1), chlorophyll b in the treatment T4 (1, 01 g mol-1) and carotenoids in treatment T6 (1.11 g mol-1). Analyzes chlorophyll fluorescence indicate that T1, T6 and T7 better performance photochemical considering all parameters (Fv/Fm , and PIABS PItotal). Concentrations of soluble sugars were higher in T1 and T2, while the starch content was higher in treatments T6 and T7. Given these results, it can be concluded that B. excelsa responded to phosphate fertilization treatments in relation to growth rates and biomass accumulation, and photosynthetic performance of the specie is closely related to the P concentration in the leaves, influenced by the efficiency of uptake and use of energy.
Keywords: Castanha-da-Amazônia; Fertilização fosfatada; Nutrição florestal